An Analysis of The Awakening Under Jung’s Archetype Theory - wang, meng yu (Pacific International Journal, 2025)
Kate Chopin (1851-1905) is a famous American female writer in the 19th century. As her masterpiece, The Awakening establishes Chopin’s position as a pioneer feminist writer. The Awakening primarily narrates the story of Edna’s vacation on Grand Isle with her husband, Léonce, and their two children. Through interactions with a typical woman, Adèle, and a young man, Robert, Edna begins to seek her self and pursue spiritual independence, but ultimately fails. It reflects the universality of women’s spiritual dilemma and the significance of self-awareness and self-construction. This paper employs Jung’s Archetype Theory to analyze the psychological growth path of the protagonist, Edna. By examining her quests for her self, the paper investigates the psychological reasons behind her tragic fate through the primary archetypes: the persona, the shadow, the anima and animus, and the self. Trapped by the persona of “the angel of the house,” Edna’s inner shadow expands, but she fails to balance her persona and shadow. Besides, Edna’s animus gradually inflates and finally out of control, leading to her lost of self. Through analysis, this paper posits that Edna’s failure in self-growth stems from her inability to manage the relationships within her personality system. Unable to combat the shadow and the burgeoning animus, Edna loses her self, succumbs mentally and commits suicide. Consequently, this paper offers insights for contemporary individuals to recognize themselves and provides guidance for shaping a balanced personality and pursuing mental well-being.